Mutation analysis of the LCE3B/LCE3C genes in Psoriasis - Soto Javier; Díaz Marta; Coto-Segura Pablo; Santos-Juanes Jorge; Coto Eliecer; Queiro Rubén; Alvarez Victoria (BMC, 2010)
Abstract Background An association between a common deletion comprising the late cornified envelope LCE3B and LCE3C genes (LCE3C_LCE3B-del) and Psoriasis (Ps) has been reported. The expression of these LCE genes was induced after skin barrier disruption and was also strong in psoriatic lesions. The damage to the skin barrier could trigger an epidermal response that includes the expression of genes involved in the formation of skin barrier. Methods We determined the LCE3C_LCE3B-del genotype in 405 Ps patients and 400 healthy controls from a Northern Spain region (Asturias). These patients and controls were also genotyped for the rs4112788 single nucleotide polymorphism, in strong linkage disequilibrium with the LCE3C_B cluster. The LCE3B and LCE3C gene variant was determined in the patients through SSCA, DHPLC, and direct sequencing. Results Allele and genotype frequencies did not differ between patients and controls for the rs4112788 and LCE3C_LCE3B-del polymorphisms. However, del/del homozygotes were significantly higher among patients with chronic plaque type Ps who did not develop arthritis (p = 0.03; OR = 1.4; 95%CI = 1.03-1.92). The analysis of the coding sequence of LCE3B and LCE3C in the patients who had at least one copy of this showed that only one patient has a no previously reported LCE3B variant (R68C). Conclusion Our work suggested that homozygosity for a common LCE3C_LCE3B deletion contributes to the risk of developing chronic plaque type Ps without psoriatic arthritis. Our work confirmed previous reports that described an association of this marker with only skin manifestations, and supported the concept of different genetic risk factors contributing to skin and joint disease.